A Progress Tracking Mobile Application for Autistic Children - Amira Aida, Zaharuddin (Universiti Malaysia Sarawak (UNIMAS), 2019)
This project proposes an interactive Android mobile application about progress tracking for autistic children. This project is developed to provide a platform for the user to keep track the progresses of the students in National Autism Society of Malaysia (NASOM). Currently, the center uses a traditional way like asserting the student's file and progress for the one to one session. One to one session is where each teacher is given a student to work on specific tasks based on the NASOM module. Additionally, from the tasks given, the teacher manually reported the status progress of the student in a progress file provided. Therefore, there is a need to integrate a mobile application for the teachers and therapist in NASOM to assist them in producing autistic children progress report efficiently using a mobile phone or tablet as a personal learning environment.